Knowledge and Practice of Contraception Use Among Females of Child-Bearing Age in Mosul, Iraq - Aldabbagh RO; Al-Qazaz HKh (Dove Medical Press, 2020)
Raghad O Aldabbagh, Harith Kh Al-Qazaz Department of Clinical Pharmacy, College of Pharmacy, University of Mosul, Ninevah 81011, IraqCorrespondence: Harith Kh Al-QazazDepartment of Clinical Pharmacy, College of Pharmacy, University of Mosul, Ninevah 81011, IraqTel +9647509158045Email harithqazaz73@yahoo.comPurpose: For thousands of years, fertility control has been used in different forms. This study was carried out to evaluate the knowledge and practice of participants regarding birth control methods with the prevalence of each method.Patients and Methods: A cross-sectional study design was employed to evaluate knowledge and practice among females. Three family-planning centers were included in addition to 2 general hospitals. A total of 440 married women between the ages of 18 and 40 years were interviewed by the first author. Self-administered version of a previously translated questionnaire was used to evaluate practice and knowledge concerning contraception use.Results: A total sample of 388 women of child-bearing age was interviewed. The mean age ± SD was 29.76 ±  6.67, while the mean number of their offspring was 4.06 ±  2.08. The intrauterine contraceptive device was the most frequently used method followed by oral contraceptive pills, while the safe-period method was the least frequently used. More than 50% of the females obtained their contraceptives from public health centers and/or hospitals. The mean number of contraception methods known by the females was 2.15 ±  1.07. Safety was the most indicated criterion for choosing the preferred method. Out of all the respondents, 86.9% indicated that they experience adverse effects from using contraceptive methods, in which a higher rate was for oral pills (31.1%), intrauterine contraceptive device (21.3%), or from both methods (18.4%).Conclusion: This study disclosed an acceptable level of knowledge and positive practices among Iraqi women seeking health-care facilities with respect to birth control methods. Females with lower levels of education require continued education and regular communication about the importance of birth control to promote the use of modern contraceptive methods. The findings from this study will help to develop programs that can improve knowledge of females and services provided by the health-care system and can reduce adverse effects from contraception and the incidence of unplanned pregnancies.Keywords: knowledge, contraception, birth control, Iraq